Analysis of a Single-Phase Transformerless Bidirectional PFC - Mei Liang; Pengyu Jia; Tengfei Guo (Energies, 2022)
This paper presents a single-phase transformerless bidirectional power factor corrector (PFC). A capacitor is inserted into a conventional full-bridge PFC by connecting the ac line terminal and a terminal of DC voltage. The functions of this inserted capacitor have two roles: to bypass the common-mode leakage current from the stray capacitor; to form an LCL filter to reduce the inductor current ripple. A hybrid modulation method is employed in this PFC. The unipolar switching scheme is applied to modulate the PFC, which can achieve high efficiency. Meanwhile, an additional modulation is inserted into the blank time of low-frequency switches to decrease the changing speed of the voltage on the inserted capacitor, and to decrease the spike on the inductor current and leakage current. The performance of the PFC is experimentally verified using a 5 kW prototype.